Synesthesia: Gluing Together Time, Number, and Space - Kadosh, R; Gertner, L (Elsevier, 2011)
This chapter describes the phenomenon of time and/or number, space (TNS) synesthesia, its possible neural mechanisms and its effect on everyday life functioning. The account for the allegedly contrasting evidence relies on the idea that both synesthetes and non-synesthetes share the same cognitive and neural mechanisms and the differences between them are down to different levels of conscious awareness and the intensity of the TNS association. Namely, synesthetes who visualize early months on the left and late months on the right were faster to make left-hand responses to the former and right-hand responses to the latter than vice versa, while synesthetes who represent early months on the right and late months on the left showed the opposite pattern. A better understanding of the neural bases might offer a lead toward its origin, including the developmental stages at which it might occur. Therefore, a careful investigation of the individual differences in the experience of TNS together with a better understanding of its neural mechanisms will provide a means for the delineation of these types of synesthesias and consequently a better knowledge of the neurocognitive mechanisms behind the implicit interaction of time, number, and space in non-synesthetes. © 2011 Elsevier Inc. All rights reserved.